KARAKTERISTIK GEOLOGI DAERAH VOLKANIK KUARTER KAKI TENGGARA GUNUNG SALAK - Suganda, Bombom Rahmat; Isnaniawardhani, Vijaya (Bulletin of Scientific Contribution, 2014)
Gunung Salak land forms hills and valleys, composed of typical volcanic deposit that controlled by geology structures. The research was conducted in several stages, there are: references study, field study or geological mapping (observation of geomorphology or landforms, rock type and genesis, geology structure indication) as well as data analysis. Landform of southeast part of Gunung Salak can be devided into steep hill geomorphological unit that lied on high land, formed by Salak volcanic deposits, with radial drainage pattern; and sloping hill geomorphology unit with smooth contours that lied on lowland, formed by Salak and Pangrango mixing volcanic deposits. The southeast part of Gunung Salak foothills from lower to upper consecutively composed by pumiceous tuf volcanic deposit; laharic breccia; lapili and pumiceous tuf with paleosoil layer intercalations; and andesitic lava. Geology structure indications was difficulty observed because of thin soil cover and sloping dip of rock layer (<10º).